Karakteristik pasien dengan preeklampsia di RSUP Prof. Dr. R. D. Kandou Manado - Hutabarat, Rien A.; Suparman, Eddy; Wagey, Freddy (Universitas Sam Ratulangi, 2016)
Abstract: World Health Organization (WHO) estimates that 585.000 women die every day from complications of pregnancy, birth process, and as a result of unsafe abortion. Maternal mortality in Indonesia was 307 of 100.000 live births and the infant mortality in Indonesia was 39 of 1000 live births. The most frequent cause of maternal mortality and fetal mortality is preeclampsia. This was a retrospective descriptive study. Data were obtained from the medical records of preeclampsia patients from January 1 until December 31, 2013 at the Department of Obstetrics and Gynecology, Prof. Dr. R. D. Kandou Hospital Manado. The results showed that there were 135 patients diagnosed with preeclampsia. There were 79 patients (58.52%) with mild preeclampsia, and 56 patients (41.48%) with severe preeclampsia. The highest frequencies were found at the age group 21-35 years (in mild preeclampsia 67.1% and in severe preeclampsia 73.2%); housewives (in mild preeclampsia 84.8% and in severe preeclampsia 78.5%); senior high school education (in mild preeclampsia 68.36% and in severe preeclampsia 76.7%); parity of multigravida (in mild preeclampsia 62% and in severe preeclampsia 59%); and interval of labor 2-5 years (in mild preeclampsia 51.02% and in severe preeclampsia 52%).Keywords: preeclampsia, characteristicsAbstrak: World Health Organization (WHO) memperkirakan 585.000 perempuan meninggal setiap hari akibat komplikasi kehamilan, proses kelahiran, dan akibat aborsi yang tidak aman. Angka kematian ibu bersalin di Indonesia adalah 307 per 100.000 kelahiran hidup dan angka kematian bayi di Indonesia adalah 39 per 1000 kelahiran hidup. Salah satu penyebab morbiditas dan mortilitas ibu dan janin adalah Preeklamsia. Penelitian ini menggunakan metode deskriptif retrospektif dengan melihat data rekam medik pasien Preeklampsia periode 1 Januari - 31 Desember 2013 di Bagian Obstetri-Ginekologi. Hasil penelitian memperlihatkan 135 pasien dengan diagnosis preeklampsia, terdiri dari 79 (58,52%) preeklampsia ringan (PER), dan 56 (41,48%) preeklampsia berat (PEB). Kelompok umur tersering ialah 21–35 tahun (pada PER 67,1% dan PEB 73,2%). Pekerjaan tersering ialah ibu rumah tangga (pada PER 84,8% dan PEB 78,5%). Pendidikan tersering ialah SMA (pada PER 68,36% dan PEB 76,7%). Jumlah paritas tersering ialah multigravida (pada PER 62% dan PEB 59%). Jarak persalinan tersering antara 2–5 tahun ( pada PER 51,02% dan PEB 52%).Kata kunci: preeklampsia, karakteristik